Optimization of specific training in volleyball for juniors - Cojocaru, A. M.; Cojocaru, M. (Science, Movement & Health, 2017)
Aim. Changes in the volleyball world, both in terms of maximizing parameters and content structure and level request players physically, mentally, bio-motility technical and tactical confirms once again the need to find the most efficient ways optimization and support capacity of performance. This study aims to determine the level of specific training subjects and assessing the effectiveness of work programs implemented to optimize training echelon competitive junior volleyball players. Methods. As a working method I used: - bibliographic documentation; - interpretation of statistical and mathematical method; - graphical representation method; Results. It is noted that both the physical evidence applied, but also the driving show an increased value of motor function in both groups included in the experiment, with more progress meant the group experiment - reflected the significant differences recorded between the averages of both groups testing final. Conclusions. Confirming the hypothesis that optimization training model - through the selection and application training pathways for specific training complex - can provide an increase in performance of junior volleyball players providing of educational objectives and the performance of the team.